2023
DOI: 10.3389/fneur.2022.1063733
|View full text |Cite
|
Sign up to set email alerts
|

A case report: New-onset refractory status epilepticus in a patient with FASTKD2-related mitochondrial disease

Abstract: ObjectivesNew-onset refractory status epilepticus (NORSE) is associated with high morbidity and mortality. Despite extensive work-up, the underlying etiology remains unknown in 50% of affected individuals. Mitochondrial disorders represent rare causes of NORSE. Biallelic variants in FASTKD2 were reported as a cause of infantile encephalomyopathy with refractory epilepsy.Case descriptionIn the study, we report a previously healthy 14-year-old with a new, homozygous FASTKD2 variant presenting with NORSE. Followi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…To gain further insights into the phenotypic spectrum associated with the FASTKD2 gene, we compiled information about all reported cases carrying variants in this gene (see Supplementary File; Supplementary Table S2). Summing up the data of the nine patients belonging to seven families with FASTKD2 variants, we found that there is high variability in both the genetic and phenotypic spectra with lactic acidosis and stroke-like episodes (MELAS) (Yoo et al, 2017;Shah and Balasubramaniam, 2021), infant-onset encephalomyopathy (Ghezzi et al, 2008;Wei et al, 2020), and new-onset refractory status epilepticus (Astner-Rohracher et al, 2023). The disease onset for P3 occurred at 7 months, whereas for all reported patients, it ranged from 6 months to 14 years.…”
Section: Resultsmentioning
confidence: 92%
“…To gain further insights into the phenotypic spectrum associated with the FASTKD2 gene, we compiled information about all reported cases carrying variants in this gene (see Supplementary File; Supplementary Table S2). Summing up the data of the nine patients belonging to seven families with FASTKD2 variants, we found that there is high variability in both the genetic and phenotypic spectra with lactic acidosis and stroke-like episodes (MELAS) (Yoo et al, 2017;Shah and Balasubramaniam, 2021), infant-onset encephalomyopathy (Ghezzi et al, 2008;Wei et al, 2020), and new-onset refractory status epilepticus (Astner-Rohracher et al, 2023). The disease onset for P3 occurred at 7 months, whereas for all reported patients, it ranged from 6 months to 14 years.…”
Section: Resultsmentioning
confidence: 92%
“…The relationship between FASTKD2 gene and mitochondrial dynamics related genes was found. FASTKD2 belongs to the protein family containing fast kinase domain, which is located in mitochondria [31] . As a component of functional protein ribonucleic acid module, FASTKD2 is an essential gene for translation and transcription in mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…63,64 Whole genome sequencing may allow the identification of the concerned variants, but muscle biopsy and skin fibroblasts could provide additional information by looking at the function of the respiratory chain complexes. 63,65 Previous recommendations suggest cutting the muscle tissue into several pieces for formalin fixation, glutaraldehyde fixation, and rapid freezing in isopentane. 65 We cannot yet provide specific recommendations for rare patients with NORSE due to mitochondrial disorders.…”
Section: Biospecimen Collection: Site and Methods Of Sample Acquisitionmentioning
confidence: 99%
“…Other biological samples might be of interest for patients with NORSE, for diagnosis or research purposes. Mitochondrial disorders were reported as a cause of NORSE for a few patients 63,64 . Whole genome sequencing may allow the identification of the concerned variants, but muscle biopsy and skin fibroblasts could provide additional information by looking at the function of the respiratory chain complexes 63,65 .…”
Section: Standard Operating Procedures For Prospective Biospecimen Co...mentioning
confidence: 99%